Bagaimana Gaya Hidup mempengaruhi Keputusan Pembelian Tiket Online - Muhammad Ashoer; Haerdiansyah Syahnur; Imaduddin Murdifin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Reflecting on netizen lifestyle and shifting behavior phenomena in e-commerce platform, this study appoints to examine the influence of lifestyle (Price-oriented, Net-Oriented, Time-Oriented, Innovative) toward e-ticket purchasing decisions in Tiket.com. A total sample of 102 respondent was stipulated refer to purposive sampling technique criterion. To measure the significance of the predictors variable, SEM (Structural Equation Model) – PLS (Partial Least Square) analysis was applied. The outcome show that Price-oriented and Time-oriented Lifestyle has no significant impact on online purchasing decision in Tiket.com and is contradict with the findings from prior research. The implications of the results are expected to enrich future studies and develop e-commerce strategies in Indonesia